Remote receiving systems for floating radar antennas - Liew, Yew Pheng. (2008)
HF radar has been studied extensively since the 1970s. HF radar is very attractive due to its physical properties, in which HF surface wave propagation is well known for the detection of targets beyond the conventional radar horizon. The 'sea-hugging' over-the-horizon capability of HFSWR allows the detection of targets beyond the line-of-sight, with reports of more than 200 nautical miles detection range for ships. As HFSWR operate in frequencies between 3 MHz and 30 MHz, corresponding to wavelengths varying from 10 m to 100 m, HFSWR would be 'anti-stealth' to most targets at such long wavelengths. The HF wave can yield up to 200 km coverage over sea, with no gap in the elevation coverage.